AMINOSALICYLATE USE IN PEDIATRIC PATIENTS WITH CROHN'S DISEASE. (26th January 2023) - Patel, Perseus; Kaplan, Jess; Moses, Jonathan; Pasternak, Brad; Samson, Charles; Suskind, David; Ali, Sabina; Adler, Jeremy
Abstract: INTRODUCTION: Societal guidelines recommend against the use of 5-aminosalicylate (5-ASA) therapy for pediatric patients with Crohn's Disease (pCD). Previous trials showed no benefit of 5-ASAs for inducing remission and similar one-year relapse rates when compared with placebo. Conversely, biologics are recommended as first-line therapy due to higher remission rates, corticosteroid-sparing effects, and potential to alter disease progression. AIMS: We aimed to describe the use of 5-ASAs in pCD and the associated patterns of biologic and corticosteroid use in a large multi-center patient cohort. METHODS: We used data from the Biologic dISContinUation sTudy (BISCUIT), a multi-center study in which retrospective medical record abstraction from 7 US centers supplemented prospectively collected data from the ImproveCareNow (ICN) Network Registry. We included patients newly diagnosed with pCD (< 18 years old) and compared patients who were prescribed a 5-ASA within 90 days of diagnosis to those who were not exposed to 5-ASAs. We used Student's t-tests, chi-squared tests, and Wilcoxon rank sum to compare baseline characteristics, including demographics (age, gender, race, ethnicity, insurance status); disease characteristics (age at diagnosis, Paris classification, concomitant liver disease, extraintestinal manifestations); and disease activity measures (labs, disease activity indices, and extraintestinal manifestations). RESULTS: Our study included 608 patients, 142 of whom (23.4%) were treated with 5-ASAs within 90 days after CD diagnosis. At baseline, younger patients (p<0.01), those with colonic disease (L2) (p=0.03), and those with Medicaid as their primary insurance (p=0.05) were more likely to receive 5-ASAs (Table 1). There was no difference in 5-ASA use by disease severity (p=0.52). Those on 5-ASA therapy had an 84-day longer delay in initiation of their first biologic medication, with 56.1% of patients starting a biologic at least 90 days after diagnosis (p<0.001). There were no differences in corticosteroid use (p=0.08) or dietary therapy (p=0.90) (Table 2). CONCLUSIONS: We found 5-ASA use was common in pCD and was associated with a near 4-month delay in initiating biologic therapy. These results are a call-to-action to improve guideline dissemination and examine barriers such as insurance status in the evidence-based treatment of pCD. Our future work will evaluate differences in outcomes, biologic durability, and disease complication rates between these groups.